Multiple Cerebral, Calcified and Infected Hydatid Cysts Case Report and Literature Review - Kouassi Jean Marie Quenum Kisito; M Laghmari; R Gana; MR Maaqili; F Bellakhdar (Journal of Neurological Research And Therapy, 2015)
Calcified and Infected Hydatid Cysts Case Report and Literature Review